SEJARAH PEMBENTUKAN DAN KEDUDUKAN UU NO 1 TAHUN 1974 TENTANG PERKAWINAN - Muda’i, Syaiful; Amirotus Sholehah, Ulyi (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2024)
Law no. 1 of 1974 concerning Marriage serves as a material law that regulates all matters concerning married life in Indonesia. This is important to do because marriage is something that must have legal force to protect the rights of the parties involved. This law goes through the history of its formation from time to time until it is promulgated in the state gazette. With this law, several things are regulated for the common good, including for women. Women's rights in marriage are increasingly regulated and protected. The marriage law which adheres to the principle of monogamy means that the practice of polygamous marriages in Indonesia must comply with applicable regulations.